Deficiency of mindin reduces renal injury after ischemia reperfusion - Tao Bai; Xiong Wang; Cong Qin; Kang Yang; Zhiguo Duan; Zhixiu Cao; Jiaqian Liang; Lei Wang; Jingdong Yuan; Pengcheng Luo (Molecular Medicine, 2022)
Abstract Background Acute renal injury (AKI) secondary to ischemia reperfusion (IR) injury continues to be a significant perioperative problem and there is no effective treatment. Mindin belongs to the mindin/F-spondin family and involves in inflammation, proliferation, and cell apoptosis. Previous studies have explored the biological functions of mindin in liver and brain ischemic injury, but its role in AKI is unknown. Method To investigate whether mindin has a pathogenic role, mindin knockout (KO) and wild-type (WT) mice were used to establish renal IR model. After 30 min of ischemia and 24 h of reperfusion, renal histology, serum creatinine, and inflammatory response were examined to assess kidney injury. In vitro, proinflammatory factors and inflammatory signaling pathways were measured in mindin overexpression or knockdown and vector cells after hypoxia/reoxygenation (HR). Results Following IR, the kidney mindin level was increased in WT mice and deletion of mindin provided significant protection for mice against IR-induced renal injury as manifested by attenuated the elevation of serum creatinine and blood urea nitrogen along with less severity for histological alterations. Mindin deficiency significantly suppressed inflammatory cell infiltration, TNF-α and MCP-1 production following renal IR injury. Mechanistic studies revealed that mindin deficiency inhibits TLR4/JNK/NF-κB signaling activation. In vitro, the expression levels of TNF-α and MCP-1 were increased in mindin overexpression cells compared with vector cells following HR. Moreover, TLR4/JNK/NF-κB signaling activation was elevated in the mindin overexpression cells in response to HR stimulation while mindin knockdown inhibited the activation of TLR4/JNK/ NF-κB signaling after HR in vitro. Further study showed that mindin protein interacted directly with TLR4 protein. And more, mindin protein was confirmed to be expressed massively in renal tubule tissues of human hydronephrosis patients. Conclusion These data demonstrate that mindin is a critical modulator of renal IR injury through regulating inflammatory responses. TLR4/JNK/NF-κB signaling most likely mediates the biological function of mindin in this model of renal ischemia.